Improving Students’ Literacy Through Co-Curricular Programs At Nyarinying Elementary School, Sumbawa Regency - Fitriani, Fitriani; Suparman, Suparman (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study examines the improvement of student literacy through the implementation of a co-curricular literacy program at Nyarinying Elementary School, Sumbawa Regency. Literacy is a basic skill that must be developed from elementary school, encompassing reading, writing, and comprehension. This study aims to describe the initial state of students' literacy skills, analyze the implementation of the co-curricular literacy program, and identify supporting and inhibiting factors that influence the program.This research employed a qualitative approach with a case study design. Subjects included the principal, co-curricular program coordinator, class teachers from grades I to VI, and selected students. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis consisted of data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and methods.The results of the study showed that before the implementation of the co-curricular program, students' literacy skills were relatively low. After the program was implemented, there was a significant increase in reading fluency, reading comprehension, writing skills, reading interest, and student self-confidence. Supporting factors included school policies, teacher commitment, the availability of literacy resources, and student enthusiasm. Meanwhile, inhibiting factors included limited time, differences in student literacy skills, limited reading materials, and suboptimal parental involvement. Overall, the co-curricular literacy program proved effective in improving students' literacy skills.